Integrated magneto–electrophoresis microfluidic chip purification on library preparation device for preimplantation genetic testing for aneuploidy detection. Issue 24 (16th April 2021) - Schneider, Lindsay; Fraser, Michelle; Tripathi, Anubhav
Abstract : Automated DNA library preparation device with microfluidic chip for DNA purification using magnetophoresis and electrophoresis. Abstract : Next generation sequencing (NGS) technology has revolutionized the field of personalized medicine through providing patient specific diagnostic information on a nucleic acid level. A key bottleneck in the NGS workflow is the preparation of nucleic acids for sequencing, or library preparation. One approach to overcoming this bottleneck on time and resources is through automating library preparation as much as possible from the stage of DNA extraction to a sequence-ready sample. Here, we have integrated microscale purification and macroscale PCR amplification to create an automated platform to replace manual DNA library preparation and magnetic bead-based cleanup steps. This microfluidic chip integrates magnetic bead transport and electrokinetic flow to remove unbound adapter dimers and other impurities from samples. We incorporate this method to develop an automated NGS DNA library preparation device that also includes macro- and microfluidic reagent movement and mixing and a thermoelectric cooler for controlled capillary heating and cooling. We greatly reduce the hands-on time, amount of pipetting required, and volumes of reagents needed as we test the feasibility of the platform on the clinically important diagnostic field of preimplantation genetic testing for aneuploidy (PGT-A). We prepared euploid and aneuploid five cell samples for sequencing and found our results were accurate for the cell samples with a sequencing quality equivalent to the standard of the DNA libraries prepared manually. Our device platform utilizes concepts such as: magneto–electrophoresis, integrated capillary PCR, and automated sample loading and unloading onto a microfluidic chip.